Hybridization of Islamic Education and Neuroscience: Transdisciplinary Studies of 'Aql in the Quran and the Brain in Neuroscience - Suyadi, Suyadi (Dinamika Ilmu, 2019)
The essence of Islamic education, in addition to the transfer of value and knowledge is the optimization of all human potential. Most of human potential rests on his brain. The science of studying the brain is neuroscience. Therefore, Islamic education and neuroscience can be hybridized in an interdisciplinary manner. The purpose of this study was to find new scientific varieties resulted from hybridization of Islamic education and neuroscience. This research is an interdisciplinary study with a qualitative approach in the form of library research. The source of the research data is the literature in the field of Islamic education and neuroscience that is explored and collected documentary and analyzed with content analysis. The results of the study showed that the concepts of nasiyah (crown) and ‘aql (mind) in the Quran have a correlation with the brain and mind in neuroscience. Both can be hybridized so as to find new varieties of science called the Islamic Education Neuroscience. This new branch of science has the potential to be equivalent to the scientific branches that have been developing so far, such as the philosophy of Islamic education, the psychology of Islamic education, the anthropology of Islamic education and so is the neuroscience of Islamic education. Educators, both teachers and lecturers who study this science can do stimulation and intervention to optimize students' brain potential in an integrated manner in learning Islamic diversity.